MARKET MECHANISMS OF DEVELOPMENT OF THE MINERAL RESOURCE COMPLEX OF KAZAKHSTAN AT THE PRESENT STAGE - Shugаiроvа, Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
This article considers the theoretical concepts of the use of market mechanisms for the development of the mineral resource complex of Kazakhstan at the present stage. It defines the features of the formation of the market of mineral resources in Kazakhstan, taking into account the mining and geological, natural resources and socio-economic features of the extraction of mineral raw materials and raw materials at the present stage. The first feature of the development of the mineral resource complex is the difference between the production factor “earth” and other natural resources. The second feature is that the mineral and raw materials production is carried out in the conditions of the natural environment. The third feature in the extraction of mineral resources is the state of working conditions and their effects on the human body. The fourth feature, objectively affecting the rise in the cost of mineral raw materials, will be a large variety of technical means necessary for its production. It has been established that the study of the market for mineral raw materials should be based primarily on a theoretical understanding of macroeconomic processes with developed market relations, taking into account the factor of globalization and the activation of the innovation component of production.